Kinematic analysis of sports movements: golf swing plane analysis - Kwon, Y. H.; Casebolt, J. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The swing plane is one of the most controversial and misleading concepts in modern golf vocabulary. Several popular swing theories in regards to the swing plane have emerged in the popular literature by golf professionals, while the majority of the biomechanical studies have been conducted based on the planar double- and triple-pendulum swing models. The purpose of this paper is to provide a comprehensive review of both the scientific and popular golf literature on golf swing mechanics in regards to the concept of swing plane.